PENGEMBANGAN E-LKPD TERINTEGRASI VIRTUAL LAB PHET INTERACTIVE SIMULATION PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Bunga Okta Ramadona; Muhammad Sofwan; Risdalina Risdalina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to Develop an Electronic Student Worksheet (E-LKPD) built on the Liveworksheets platform and integrated with the PhET Interactive Simulation virtual lab as an instructional medium for Natural and Social Sciences (IPAS) learning on the topic of Energy and Its Transformation for fourth-grade elementary school students. The study was motivated by the limited availability of interactive and contextual digital learning media, which has contributed to low student engagement and insufficient conceptual understanding in IPAS learning. This study employed a Research and Development (R&D) method, which is a research approach used to produce a specific product while simultaneously testing its feasibility and effectiveness. Product Development followed the DDD-E model (Decide, Design, Develop, Evaluate). Data collection instruments included expert validation sheets and student response questionnaires. Validation results showed that the E-LKPD received feasibility scores of 95,45% from the media expert, 87.71% from the subject matter expert, and 98% from the language expert, all of which fall within the